1973
DOI: 10.1128/aac.4.3.294
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Effects of Aphidicolin, a New Antibiotic Produced by Cephalosporium aphidicola

Abstract: Aphidicolin is an antibiotic of novel structure produced by the mold Cephalosporium aphidicola . It is a potent inhibitor of cellular deoxyribonucleic acid synthesis, and it also strongly inhibits the growth of herpes simplex virus both in tissue culture and in the rabbit eye. Aphidicolin is active against iododeoxyuridine-resistant herpes virus, and does not itself readily induce the formation of drug-resistant strains of herpesvirus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
0
1

Year Published

1979
1979
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(76 citation statements)
references
References 6 publications
2
73
0
1
Order By: Relevance
“…The drug inhibits cell division, cellular DNA synthesis and repair replication in a number of manmmalian cells without affecting RNA synthesis or protein synthesis (2,3,4). The multiplication of herpes virus, vaccinia virus and SV40 is also sensitive to aphidicolin (1,4,20). Recently it has been reported that DNA polymerase a from various sources is strongly inhibited by low concentrations of aphidicolin while DNA polymerase 0 and y are resistant to drua concentrations up to 10-3 M (2,3,4,5,17,20).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The drug inhibits cell division, cellular DNA synthesis and repair replication in a number of manmmalian cells without affecting RNA synthesis or protein synthesis (2,3,4). The multiplication of herpes virus, vaccinia virus and SV40 is also sensitive to aphidicolin (1,4,20). Recently it has been reported that DNA polymerase a from various sources is strongly inhibited by low concentrations of aphidicolin while DNA polymerase 0 and y are resistant to drua concentrations up to 10-3 M (2,3,4,5,17,20).…”
Section: Introductionmentioning
confidence: 99%
“…a tetracyclic terpenoid isolated from the fungus Cephalosporium Aphidicola (1). The drug inhibits cell division, cellular DNA synthesis and repair replication in a number of manmmalian cells without affecting RNA synthesis or protein synthesis (2,3,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, we have used aphidicolin [16], a specific inhibitor of the a-like DNA polymerase of higher plant cells [17], as well as that of the DNA polymerase t~ of animal cells [4,6,9,18].…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
“…Huberman, 1981) and this conclusion is not unexpected. In addition, there are previous reports of the inhibition of HSV growth (Bucknall et al, 1973) and DNA polymerase activity by aphidicolin (Pedrali-Noy & Spadari, 1979Dicioccio et al, 1980). However, detailed studies of the mode of action of this interesting inhibitor on cellular ~-polymerases are likely to be constrained by the difficulties of acquiring the relevant genetic information.…”
Section: Discussionmentioning
confidence: 99%